Z Leśmiana - Noszczyk, Michał (Śląskie Studia Polonistyczne, 2014)
Z Leśmiana is a text devoid of any provocativeness; it is a short, traditional piece of prose. It has only one nameless female protagonist, because – as is the author’s intent – she reveals the feminine side of his soul. The story is related to a “discursive” text, because Michał Noszczyk – in the case he did not manage to finish his speech for the National Memetic Scientific Workshop – was to read this piece of poetic prose (or at least, suggest reading it to the participants). It seems fitting, inasmuch his – the author’s – main prop (along with the red shoes) is a cellphone.